PRODUCTIVE FOREST RECOVERY IN LEGAL RESERVE AREA: A CASE STUDY IN EASTERN AMAZON - Pereira, Paulo Cezar Gomes; Siviero, Marco Antonio; Ruschel, Ademir Roberto; Vieira, Sabrina Benmuyal; Sales, Agust; Siqueira, Maria Lucia Marques (Floresta, 2024)
This study aimed to evaluate a model for Legal Reserve (LR) recovery based on a mixed timber production system (planting + natural regeneration) in the eastern Amazon, state of Pará. For data collection, seven plots of 50 m x 20 m were established, and all individuals with DBH (diameter at breast height) ≥ 5 cm were inventoried. Species diversity, horizontal structure, and commercial wood production were assessed at 13 years of age. A total of 103 species were found, distributed among 69 genera and 33 families. The population density was 1,425 individuals per hectare, and dominance corresponded to 19.45 m².ha-1. The total wood volume was 121.4 m³.ha-1, with 63.3 m³.ha-1 coming from the planted species (S. parahyba var. amazonicum) and 58.1 m³.ha-1 from natural regeneration. Among the regenerating species, Cecropia distachya showed the highest values for the evaluated parameters. The adopted model showed potential for use in LR environmental recovery, reconciling this action with revenue generation through silvicultural interventions that can be applied to the stand, aiming for wood production. To achieve this, adjustments to the regulations governing the forest management of recovering areas are necessary.